Mission and Development in Manggarai, Flores Eastern Indonesia in 1920-1960s (History Department, Semarang State University and Historian Society of Indonesia, 2019)
This paper explores the mission and development in Manggarai Flores, Indonesia in 1920-1960s. These two activities were carried out by Catholic Church missionaries from Europe. Before this religion came to Manggarai, this region was in an isolated and backward condition. People lived in primitive way of life. The new development was carried out with the arrival of the Dutch colonists who worked closely with the Catholic Church missionaries beginning in the early 20th century. The Church utilized the support of the Dutch colonialists while running various development programs as important strategies to gain sympathy from the Manggarai people. As a result, the Church was accepted and became the dominant force in the community. This proves that missions that are in line with development or religion which at the same time pay attention to religious and secular aspects can win the hearts of the people. By using the historical approach, this paper aims to present a history of mission and development relations in Manggarai, Eastern Indonesia while providing a critical analysis of how religion, government and society are interwoven.Â Paper ini mengeksplorasi misi dan pembangunan di Manggarai Flores, Indonesia tahun 1920-1960s. Dua aktivitas ini dilakukan oleh misionaris Gereja Katolik yang berasal dari Eropa. Sebelum agama ini datang ke Manggarai, wilayah ini berada dalam kondisi terisolasi dan terkebelakang. Masyarakat tidak mengenal infrastruktur modern. Pembangunan baru dilakukan dengan datangnya penjajah Belanda yang bekerja sama erat dengan misionaris Gereja Katolik mulai pada awal abad 20. Gereja memanfaatkan dukungan Belanda sekaligus menjalankan aneka program pembangunan sebagai strategi penting untuk mendapatkan simpati orang Manggarai. Hasilnya Gereja diterima dan menjadi kekuatan dominan di dalam masyarakat. Hal ini membuktikan bahwa misi yang sejalan dengan pembangunan atau agama yang sekaligus memperhatikan aspek religius dan kultural dapat memenangkan hati masyarakatnya. Dengan menggunakan pendekatan historis, artikel ini bertujuan untuk menyajikan sejarah hubungan misi dan pembangunan di Manggarai, Indonesia Timur sambil memberikan analisis kritis tentang bagaimana agama, pemerintah dan otoritas masyarakat terjalin erat.Â